Metabolic profile of mycobacterium smegmatis reveals Mce4 proteins are relevant for cell wall lipid homeostasis - Santangelo, María De La Paz (2016)
Introduction The Mce proteins are encoded in a variable number of operons (from one to eight) in all Mycobacterium species. A role in the transport of host and mycobacterial lipids has been demonstrated for some Mce proteins in the pathogen Mycobacterium tuberculosis but little is known about these proteins in Mycobacterium smegmatis, a soil dweller species. Objective To investigate the role of Mce proteins in M. smegmatis.